Neurofilament Light Chain Levels in Multiple Sclerosis Correlate With Lesions Containing Foamy Macrophages and With Acute Axonal Damage - Aletta M.R. van den Bosch; Nina L. Fransen; Matthew R. J. Mason; Annemieke Johanna Rozemuller; Charlotte E. Teunissen; Joost Smolders; Inge Huitinga (2022)
Background and Objectives To investigate whether white matter lesion activity, acute axonal damage, and axonal density in MS associate with CSF neurofilament light chain (NfL) levels. Methods Of 101 brain donors with MS (n = 92 progressive MS, n = 9 relapsing-remitting MS), ventricular CSF was collected, and NfL levels were measured. White matter lesions were classified as active, mixed, inactive, or remyelinated, and microglia/macrophage morphology in active and mixed lesions was classified as ramified, ameboid, or foamy. In addition, axonal density and acute axonal damage were assessed using Bielschowsky and amyloid precursor protein (APP) (immune)histochemistry. Results CSF NfL measurements of donors with recent (<1 year) or clinically silent stroke were excluded. CSF NfL levels correlated negatively with disease duration (p = 6.9e-3, r = 0.31). In donors without atrophy, CSF NfL levels correlated positively with the proportion of active and mixed lesions containing foamy microglia/macrophages (p = 9.85e-10 and p = 1.75e-3, respectively), but not with those containing ramified microglia. CSF NfL correlated negatively with proportions of inactive (p = 5.66e-3) and remyelinated lesions (p = 0.03). In the normal appearing pyramid tract, axonal density negatively correlated with CSF NfL levels (Bielschowsky, p = 0.02, r = −0.31), and the presence of acute axonal damage in lesions was related to higher NfL levels (APP, p = 1.17e-6). The amount of acute axonal damage was higher in active lesions with foamy microglia/macrophages and in the rim of mixed lesions with foamy microglia/macrophages when compared with active lesions containing ramified microglia/macrophages (p = 4.6e-3 and p = 0.02, respectively), the center and border of mixed lesions containing ramified microglia/macrophages (center: p = 4.6e-3, border, p = 4.6e-3, and n.s., p = 4.6e-3, respectively), the center of mixed lesions containing foamy microglia/macrophages (p = 4.6e-3 and p = 0.02, respectively), inactive lesions (p = 4.6e-3 and p = 4.6e-3, respectively), and remyelinated lesions (p = 0.03 and p = 0.04, respectively). Discussion Our results demonstrated that active and mixed white matter MS lesions with foamy microglia show high acute axonal damage and correlate with elevated CSF NfL levels. Our data support the use of this biomarker to monitor inflammatory demyelinating lesion activity with axonal damage in MS.